Perlindungan Hukum terhadap Lagu Daerah yang Tidak Diketahui Penciptanya - Berthon Jonathan (University Of Bengkulu Law Journal, 2019)
The cultural wealth is the result of high Indonesian creativity and is an intellectual property that must be protected and developed. The entire territory of Indonesia from Sabang to Merauke has its own cultural characteristics. Each region has regional songs, regional dances, regional crafts that make tourists from various countries come to Indonesia because of interest to see directly our culture is even studied in depth. The Indonesian People have high creativity that becomes a strong interest and can only be found in Indonesia. There are some new things that have not previously been set and updated in the old Copyright Law. One of the new ones is the regulation of Traditional Cultural Expressions that have not been clearly defined in the Copyright Law. There is no explanation of Traditional Knowledge and Expressions of Traditional Culture and Orphan Works.